Suara Minangkabau : sejarah dan bibliografi akhbar dan majalah di Sumatera Barat, 1900-1941 - Ahmat Adam. (Kuala Lumpur : Penerbit Universiti Malaya, 2012)
History and bibliography of newspapers and periodicals in Sumatera Barat, Indonesia from 1900 to 1941.